FIELD BOOK OF PLANT PRODUCTION WITH SPECIAL REFERENCE TO ORGANIC PRODUCTION - Filipović, Vladimir; Ugrenović, Vladan; Radivojević, Stevan (Economics of Agriculture, 2011)
The necessity of maintaining records in existing production systems, imposes the need for adequate training and application by primary producers, in order to avoid any unwanted events in food production. Many cases of breaking of the prescribed norms result in a situation where partcipants in the chain, due to negligence and lack of adequate documentation, bear the consequences of such behaviour. Therefore, the establishing of the Field book of plant production would create the conditions for a higher degree of control and supervision over all operations performed and measures taken during the production process, both in feld crop and vegetable production, and other kinds of plant production. Its primary purpose is for the needs of keeping records in organic feld production, but also in all other types of plant production. The Field book includes numerous data relevant for the production itself (year, plant species, areas, etc.). In this way, the Field book of plant production enables easy entry and analysis of obtained data, which in the long term represents a signifcant material for planning new types and kinds of production.